EFFICIENCY OF ROSREESTR AS A FACTOR IN INCREASING RUSSIA’S INVESTMENT ATTRACTIVENESS - Ulitskaya, Natalya; Akimova, Maria; Ulitskaya (Revista Inclusiones, 2020)
Attracting investments is one of the main objectives of modern society. High investment attractiveness is the main condition for increasing the country’s competitiveness, ensuring high and sustainable rates of social and economic growth. To find ways for attracting investment in real estate, it is necessary to conduct research on the role of agencies working in land and property relations. The article aims to analyze the work of Rosreestr (The Federal Service for State Registration, Cadastre and Cartography) as a factor in Russia’s investment attractiveness, including the "property registration" indicator. The scientific conceptual approach was chosen as the main one to study this problem as it demonstrates the influence of Rosreestr on business development, along with dynamic indicators of investment attractiveness of Russia and its regions. In this study the authors reveal the theoretical aspects of the impact that registration activities with real estate have on the investment attractiveness of the country. The study presents the dynamics of foreign direct investment and classifies the main factors of Russia’s investment attractiveness.